(untitled) (African Journal of Biomedical Research, 2021)
Psychotherapy as a treatment modality for mental illness is recognized worldwide, however there are different perceptions and opinions about its practice and usefulness in treating mental illness in medical students. This present study assessed the knowledge and perception of final year medical students about psychotherapy. This study was a cross sectional survey done amongst final year Medical students of the University of Ilorin during their psychiatry posting, using a semi-structured questionnaire designed by the researchers. A total of one hundred and thirty students participated fully in the study. More than half of students (58.5%) who participated in the study reported that they first heard about psychotherapy during the psychiatry posting, while about 26.1% of them first heard of psychotherapy from the media. Sixty percent of respondents believed everybody needs some form of psychotherapy, while 18.5% believed only the mentally ill needs psychotherapy. Sixty out of the 130 respondents considered psychotherapy to be better than medications in the treatment of mental illness, while 23% of respondents still thought psychotherapy involved some form of brain-washing. However, 95% of them would consider a research in to the field of psychotherapy in the future, while 73% will consider training in psychotherapy if opportunity arises. The knowledge and perception of medical students about psychotherapy is important in order to gauge the quality of medical education concerning this treatment modality as well as help to suggest possible areas of additional focus for medical tutors.